Innovation, Demand, and Responsibility: Some Fundamental Questions About Health Systems; Comment on "What Health System Challenges Should Responsible Innovation in Health Address? Insights From an International Scoping Review" - Harro van Lente (Kerman University of Medical Sciences, 2019)
In this commentary on the exercise of Lehoux et al (this volume) I argue that in discussions on the current challenges of health systems, a better diagnosis of the health system is required. The cause of responsible innovation in health (RIH) requires a better understanding of the dynamics of health systems, in particular how innovation, demand, and responsibility are manifested. Innovation brings its own dynamic to the health system; demands are linked to historical and social developments; responsibility brings contestations about what counts as good healthcare. Any attempt of RIH should include such reflections.